Thinking about connectivity and electronality in the days of COVID-19: WhatsApp and the communicative model of autism - Reaño Carranza, Ernesto (2020)
The theory of electronality as it has been linked to autism, establishes that this stage of our communicational history, where the use of the electronic word prevails through technologies born from cybernetics and the internet, offers tools that not only favor greater fluidity for an autistic type of mind but benefit the general population. In these times of quarantine as a result of the COVID-19, it has been necessary to promote a greater use of tools and applications that favor remote communication, an use for which we have noticed that autistic people seem to be better prepared due to the forms of processing. This leads to thinking about the relationships between the autistic mind and the new information technologies. This article will show the relationships between the autistic mind and the configuration of current communication models focused more on connectivity than dialogue. It also proposes a reflection on what the autistic mind teaches us about new ways of interacting.